Sulfur-doped graphene laminates for EMI shielding applications - Shahzad, Faisal; Kumar, Pradip; Yu, Seunggun; Lee, Seunghwan; Kim, Yoon-Hyun; Hong, Soon Man; Koo, Chong Min (ROYAL SOC CHEMISTRY, 2015)
Herein, for the first time, we demonstrate that a laminated structure of sulfur-doped reduced graphene oxide (SrGO) provides significant potential for electromagnetic interference shielding applications. In this study, SrGO was prepared through the reaction between graphene oxide and hydrogen disulfide (H2S) gas at elevated temperatures. The doping degree of S was controlled through varying the time and temperature of the reaction and the maximum doping content of 5.6 wt% was achieved. Because of the n-type doping contribution of the S atom to the doped graphene, SrGO laminate not only revealed a 47% larger electrical conductivity (75 S cm(-1)) than undoped reduced graphene oxide laminate (51 S cm(-1)) but also revealed 119% larger EMI shielding effectiveness (33.2 dB) than the undoped one (15.5 dB) at the same sample thickness.
Keywords: COMPOSITE FOAMS; OXIDE; LIGHTWEIGHT; PERFORMANCE; REDUCTION; ELECTROCATALYST; NANOCOMPOSITE